If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(7x + 5) = 8x + 2(x + -3) Reorder the terms: 3x + -1(5 + 7x) = 8x + 2(x + -3) 3x + (5 * -1 + 7x * -1) = 8x + 2(x + -3) 3x + (-5 + -7x) = 8x + 2(x + -3) Reorder the terms: -5 + 3x + -7x = 8x + 2(x + -3) Combine like terms: 3x + -7x = -4x -5 + -4x = 8x + 2(x + -3) Reorder the terms: -5 + -4x = 8x + 2(-3 + x) -5 + -4x = 8x + (-3 * 2 + x * 2) -5 + -4x = 8x + (-6 + 2x) Reorder the terms: -5 + -4x = -6 + 8x + 2x Combine like terms: 8x + 2x = 10x -5 + -4x = -6 + 10x Solving -5 + -4x = -6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -5 + -4x + -10x = -6 + 10x + -10x Combine like terms: -4x + -10x = -14x -5 + -14x = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 -5 + -14x = -6 + 0 -5 + -14x = -6 Add '5' to each side of the equation. -5 + 5 + -14x = -6 + 5 Combine like terms: -5 + 5 = 0 0 + -14x = -6 + 5 -14x = -6 + 5 Combine like terms: -6 + 5 = -1 -14x = -1 Divide each side by '-14'. x = 0.07142857143 Simplifying x = 0.07142857143
| 2x+21+4x+15=x | | 2(-3x+4)-3(3-3x)=44 | | 11a*2+a+6a*3+9a*2+9= | | f(x)=x-2x-2 | | 65.95+12=275.80 | | 17+p=3(13-p) | | X(35-2x)+X(35-2x)+(70-2x)(x)+(70-2x)(x)= | | 21=-7/9y | | -4(7p+7)=-53 | | 11+17x=6x+8 | | 3(2x-1)-6=-51 | | 17x-1=44x-2 | | Z^2+(-3+2i)z+5-i=0 | | 17x-1=44x-3 | | 6x+8+2x+4=180 | | X+65=x+125 | | 10=-2m+b | | 7n+17=59 | | -4x+11g= | | 256/65536 | | 3b^4a^7/12b^4a^2 | | 4x-2=4+x | | -5/2x=10 | | x/(x-5)=3/7 | | 3n-5=-8(6+5h) | | 7s+12t=107 | | 4x+1+100=11+19x | | 33k-7(k+9)=4(k-55)-8 | | 11y-6x=26 | | 4x+3+2x+4= | | 8-9(y+4)+6=-2 | | 12x+172=2x+4 |